Peran Layanan Digitalisasi Perpustakaan di Lingkungan Balai Pendidikan dan Pelatihan Keagamaan Kota Bandung - Ahmad Husni Hamim (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
Digitalization is the process of transferring media from a printed form to a digital form. Digitalization is done to create digital archives, photocopying, and for digital library collections. The development of library information technology in educational and training institutions is endeavored by an exellent service for the users, this is not enough in the conventional way. Currently the latest development is very remarkable related to digital libraries (digital library) which has advantages in the speed of management or accessing oriented to digital data and computer network media (internet).